2007
DOI: 10.1111/j.1365-2788.2007.00977.x
|View full text |Cite
|
Sign up to set email alerts
|

The behavioural phenotype of Cornelia de Lange Syndrome: a study of 56 individuals

Abstract: The behavioural characteristics identified in our sample were correlated with some clinical and functional aspects (chronological age, cognitive level and clinical phenotype). The variability of the behavioural profile in CdLS reflected the wide variability in cognitive and adaptive functioning across individuals and led us to conclude that there may be multiple behavioural phenotypes associated with the syndrome. Further comparative studies between CdLS and individuals with intellectual disability or other ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
101
6
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(124 citation statements)
references
References 30 publications
14
101
6
2
Order By: Relevance
“…F, female; M, male; NA, information not available*Common features for Cornelia de Lange syndrome (CdLS) 20 21 23 54…”
Section: Resultsmentioning
confidence: 99%
“…F, female; M, male; NA, information not available*Common features for Cornelia de Lange syndrome (CdLS) 20 21 23 54…”
Section: Resultsmentioning
confidence: 99%
“…A small number of previous studies have evaluated sleep in adults and children with CdLS and there are conflicting findings regarding the incidence of sleep disturbance as well as its relation to behavioral problems. Approximately 12-72% of individuals with CdLS experience problems with sleep including settling and waking at night although most studies are limited in their characterization of the disturbances [3,4]. There has not yet been a study evaluating sleep disordered breathing or obstructive sleep apnea in this population.…”
Section: Introductionmentioning
confidence: 94%
“…However, the association between CdLS and ASD has recently received more attention. Prevalence rates of autism in CdLS range from 50 -67% Basile, Villa, Selicorni & Molteni, 2007;Berney, et al, 1999;Bhyuian et al, 2006, Moss et al, 2008. Using the Childhood Autism Rating Scale (CARS; , Oliver et al (2008) reported that 32.1% of 54 individuals with CdLS scored within the 'severe autism' category of the CARS compared to only 7.1% of a matched control group of individuals with intellectual disability, suggesting that the relationship between CdLS and ASD is not solely accounted for by associated degree of disability.…”
Section: Autism Spectrum Disorder In Cornelia De Lange Syndromementioning
confidence: 99%